The Effects of Web-Based Technologies on Marketing Activities of Professional Sports Clubs - Serdar Samur (Journal of Educational Issues, 2024)
The global market’s economic growth has been boosted by the size of the sports industry, which now has a budget in the billions of dollars. Sports marketing has emerged as a result of this growth in the sports industry. Sports marketing has emerged as the most important feature of sports companies, having grown in importance as a scientific discipline. Inside the industry, sports clubs have started to search for ways to increase their market share in both national, and foreign markets.The industry’s ongoing growth has resulted in an increase in the number of goods, and services available, as well as a competitive climate. The purpose of this study is to identify innovations in web-based technology used by sports clubs to market their goods, and services to target audiences.The research was carried out in accordance with the standards of qualitative research. Search engines, blogs, forums, podcasts, press bulletins, e-mail, and content sharing sites are the most commonly used web-based technologies by sports clubs, according to the results of the study.